2010
DOI: 10.1161/circinterventions.109.900779
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Predictors of Plaque Rupture in the Peripheral Arteries

Abstract: Background-Plaque rupture may be present in the peripheral arteries of the patients at high risk for cardiovascular events and is possibly associated with vascular vulnerability. Methods and Results-One hundred one iliofemoral arteries from 101 patients undergoing angioplasty were studied.Intravascular ultrasound imaging was performed before intervention. Plaque rupture was defined as presence of a cavity that communicated with the lumen with an overlying residual fibrous cap fragment. Incidence, numbers, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…This discordance between plaque severity and inflammatory response in the AAs was unexpected but corroborates previously published human data. Clinical studies have shown that systemic inflammation defined by CRP levels is greater in patients with COR atherosclerosis and evidence of plaque rupture, whereas the largest study to assess peripheral plaque rupture in the iliofemoral arteries showed no such association with CRP levels . By showing that AA lesion area correlates with levels of plasma glucose while COR lesion area does not, it appears that disease severity in the AAs is directly related to hyperglycemia while in the CORs this is not the case.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This discordance between plaque severity and inflammatory response in the AAs was unexpected but corroborates previously published human data. Clinical studies have shown that systemic inflammation defined by CRP levels is greater in patients with COR atherosclerosis and evidence of plaque rupture, whereas the largest study to assess peripheral plaque rupture in the iliofemoral arteries showed no such association with CRP levels . By showing that AA lesion area correlates with levels of plasma glucose while COR lesion area does not, it appears that disease severity in the AAs is directly related to hyperglycemia while in the CORs this is not the case.…”
Section: Discussionmentioning
confidence: 95%
“…Clinical studies have shown that systemic inflammation defined by CRP levels is greater in patients with COR atherosclerosis and evidence of plaque rupture, whereas the largest study to assess peripheral plaque rupture in the iliofemoral arteries showed no such association with CRP levels. 15 16 By showing that AA lesion area correlates with levels of plasma glucose while COR lesion area does not, it appears that disease severity in the AAs is directly related to hyperglycemia while in the CORs this is not the case. A potential explanation is that the presence of hyperglycemia indirectly drives atherosclerosis development and progression in the CORs via an effect on inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…However, other investigators have reported correlations between PAD atherosclerosis and IVUS in the femoral arteries, 26 and IVUS has been reported in PAD patients for identifying plaque rupture. 20 Other studies have compared IVUS and angiography for assessment of vessel and lumen dimensions and for plaque morphology in PAD patients. 19 Two major reviews discussed the applications of IVUS in PAD patients, specifically for assessment of vessel dimensions and plaque morphology.…”
Section: Limitationsmentioning
confidence: 99%
“…Although vulnerable plaques were investigated in patients with PAD, coverage was limited to a segment of less than 3 cm of the SFA (40) because the acquisition of multicontrast images is challenging given the large number of images needed to cover the entire vascular territory of the leg; the same holds true for alternative approaches. Nevertheless, recent studies using intravascular ultrasound (US) (41) suggest that the identification of vulnerable plaques or plaque ruptures in PA is potentially important in terms of patient management and prognosis. Okura et al found that there was a significant association between plaque rupture in iliofemoral arteries in patients with severe PAD and high prevalence of history of acute coronary syndrome.…”
Section: Discussionmentioning
confidence: 99%